Maternal complications in eclampsia and pre-eclampsia: an institutional study - Konnur, Harsha; Modi, Shilpa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Preeclampsia and eclampsia are associated with higher rates of maternal, fetal, and infant mortality, and severe morbidity, especially in cases of severe preeclampsia, eclampsia, and HELLP syndrome. The aim of the study was to determine maternal outcomes in pregnant women with severe preeclampsia and eclampsia. Methods: This was a retrospective descriptive study carried out at Vaatsalya Life Hospital, a tertiary hospital in Kalaburagi, Karnataka from January 2016 to June 2018. All patients admitted with preeclampsia and eclampsia were analysed for the maternal complications. Results: A total of 100 deliveries were conducted during the study period of which 71 cases were severe preeclampsia and eclampsia. Most of the patients were primi parous with mean age of 26.5 years. There were 32 cases of severe preeclampsia and 39 cases of eclampsia. The most common complication was HELLP syndrome in 6 cases (2 with ARF). There was one case of maternal mortality. Conclusions: We conclude that severe preeclampsia and eclampsia are associated with higher rates of maternal severe morbidity and that these two factors still remain the major contributors to maternal morbidity and mortality.